STUDI EMPIRIS ATAS ABSOLUTE INCOME HYPOTHESIS DAN PERMANENT INCOME HYPOTHESIS DALAM PERSPEKTIF ISLAM - Anton Bawono (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
Conventional consumption theory has complementary development and correct to one another. In this study, the aims include religiosity variable determinant of consumption, the household consumption behavior of Muslims. The analysis tool used is multiple regressions. Research findings indicate that religiosity variables have the most dominant and significant influence. While the other variables are also significant is the variable income, wealth and the wealth of productive smoothly the current period. The most dominant religiosity variable coefficients, because the more religious a Muslim will increasingly think of consumption the interests others in need, as it has a good prospect in the world in life and after death, in accordance with the guidance in the Qur’an and the Sunnah of the Prophet.